INFECTION OF CONTRACAECUM SP. LARVAE (NEMATODA: ANISAKIDAE) IN TILAPIA OREOCHROMIS NILOTICUS OF PERU - Chiclla-Salazar, Armando (2015)
This study aimed to report the infection of L3 larvae of Contracaecum sp. (Nematoda: Anisakidae) in Oreochromis niloticus Linnaeus, 1758 (Pisces: Cichlidae) in two Huaura's lagoons, Lima, Peru. 21 specimens of O. niloticus were collected, 19 specimens were infected by Contracaecum sp. in the intestine and the coelomic cavity. Ecological indicators (abundance, prevalence and mean intensity) and the relations of sex, length, width, and weight and sampling site of the fish for all parasites found were analyzed. Prevalence was 78% and mean intensity and abundance were 7.2 and 6.9, respectively. An approximation of the role of the parasite in infections registered in man by accidental consumption of fish with anisakidos was conducted.